Confidence-Enhanced Performance - Compte, Olivier; Postlewaite, Andrew (American Economic Review, 2004)
There is ample evidence that emotions affect performance. Positive emotions can improve performance, while negative ones can diminish it. For example, the fears induced by the possibility of failure or of negative evaluations have physiological consequences (shaking, loss of concentration) that may impair performance in sports, on stage, or at school. There is also ample evidence that individuals have distorted recollection of past events and distorted attributions of the causes of success or failure. Recollection of good events or successes is typically easier than recollection of bad ones or failures. Successes tend to be attributed to intrinsic aptitudes or effort, while failures are attributed to bad luck. In addition, these attributions are often reversed when judging the performance of others. The objective of this paper is to incorporate the phenomenon that emotions affect performance into an otherwise standard decision theoretic model and show that in a world where performance depends on emotions, biases in information processing enhance welfare.